2016
DOI: 10.1093/annonc/mdw220
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, phase III trial of palonosetron versus granisetron in the triplet regimen for preventing chemotherapy-induced nausea and vomiting after highly emetogenic chemotherapy: TRIPLE study

Abstract: UMIN000004863.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 13 publications
0
62
1
1
Order By: Relevance
“…In general, previous phase III trials of antiemetics use a complete response ratio in the overall phase or delayed phase after the first course for each patient as a true endpoint 14, 15. In our opinion, however, there is no rationale to speculate that the present surrogate endpoint is not an appropriate assessment for antiemetic efficacy, as pharmacists reviewed all outpatients to assess CINV and other adverse events induced by chemotherapy, and consulted physicians to modify salvage antiemetic therapy as needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, previous phase III trials of antiemetics use a complete response ratio in the overall phase or delayed phase after the first course for each patient as a true endpoint 14, 15. In our opinion, however, there is no rationale to speculate that the present surrogate endpoint is not an appropriate assessment for antiemetic efficacy, as pharmacists reviewed all outpatients to assess CINV and other adverse events induced by chemotherapy, and consulted physicians to modify salvage antiemetic therapy as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, no patients discontinued chemotherapy because of CINV in this study. Palonosetron, a second-generation 5-HT 3 RA, has a longer half-life than other first-generation 5-HT 3 RAs and is also effective against delayed phase CINV for highly emetogenic chemotherapy 14, 15. In Japan, palonosetron dosing is approved at 0.75 mg, 3-fold higher than in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, Suzuki et al reported a CR rate for palonosetron combined with dexamethasone and aprepitant in patients receiving high emetic risk chemotherapy (HEC) of 68% [7].…”
Section: Discussionmentioning
confidence: 98%
“…The 5HT 3 receptor antagonist called palonosetron has a superior inhibitory effect on CINV in the delayed phase compared to another such drug, granisetron 9 , thus we used palonosetron in this study. During the rst course of chemotherapy, all patients received oral aprepitant 125 mg, intravenous dexamethasone 9.9 mg, and intravenous palonosetron 0.75 mg before chemotherapy on day 1.…”
Section: Antiemetic Treatmentmentioning
confidence: 99%